Assessing the suitability of tree species for urban green space in a tropical university campus in Surakarta, Indonesia - INGGRID TRIFENA YULIA; DINDA PUTRI PERMATASARI; IGUSTITA IGUSTITA; GAVRIEL ENOS BERLIN; RAISA NOOR SAFIRA; SUGIYARTO SUGIYARTO; IRFAN ABU NAZAR; WIDHI HIMAWAN; SUNARTO SUNARTO; PRAKASH PRADHAN; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Yulia IT, Permatasari DP, Igustita, Berlin GE, Safira RN, Sugiyarto, Nazar IA, Himawan W, Sunarto, Pradhan P, Setyawan AD. 2023. Assessing the suitability of tree species for urban green space in a tropical university campus in Surakarta, Indonesia. Biodiversitas 24: 1713-1723. The presence of tree vegetation plays an important role in urban ecosystem. It provides various ecological and sociocultural functions from comforting micro-climates to beautification of the landscape. The central campus of Universitas Sebelas Maret (UNS) in Kentingan, Surakarta City, Central Java, Indonesia, has various tree species that grow well and become a constituent part of the campus area. This central campus environment has been considered one of the urban forests for city of Surakarta. This study aimed to determine the tree diversity occurring in the campus area of Universitas Sebelas Maret and to assess the suitability of the tree species based on silviculture, management and aesthetic aspects. Data collection was conducted by field observations at four stations: east, west, north, and south. Across the stations, the name of the tree species with minimum diameter breast height of 10 cm, the size of the tree’s circumference, the coordinates of the location of the tree, and tree’s morphological characteristics were documented. Each tree was then assessed for suitability for urban green space by scoring based on several silviculture, management and aesthetic criteria indicators. The results found 106 tree species in the studied area. Among them, 69 species (65%) had high suitability level, while 34 other species (32%) and 3 species (3%) were in the medium and low category, respectively. Some species with the highest score of 45 were kayu putih (Melaleuca leucadendra (L.) L), mimba (Azadirachta indica A.Juss.) and nyamplung (Calophyllum inophyllum L.), while the lowest score of 28 was kamboja (Plumeria acuminata W.T.Aiton). Species with high score are therefore recommended to be used in urban green space in the university area, and vice versa. The findings of this study suggest that vegetation suitability planning can be carried out to ensure the sustainability and balance of ecological functions of urban green space.